Sex Ratios, Sexual Dimorphism, Body-Weight and Moisture Content in Two Desert Termites, Anacanthotermes Macrocephalus (Hodotermitidae) and Microteremes Mycophagus (Termitidae), from India - Roonwal, M L; Rathoe, N S (Annals of Arid Zone, 2016)
Sex Ratios : Among 1284 swarming imagoes in Anacanthotermes mocrocephalus (Desn.) males predominate in the ratio of ♂9: ♀7.7 (range♂535-68%, ♀32-46.5%). Similarly, in Microtermes mycophagus (Desn.) among 689 imagoes, males predominate in the ratio of ♂4.1 :♀3 (range ♂57.1-62.9%, ♀37.1-42.9%). Sexual Dimorphism: In deal ate imagoes of A. macrocephalus the sexes do not differ in respect of either the total length (without wings) or the maximum head-width, but the abdomen is slightly wider in females than in males. No sexual difference is noticeable in the body-weight of dealates (♂48.0-55.8 mg., ♀47.0-59.8 mg.). In M. mycophagus the total length (with wings) and the head-width show no appreciable sexual differences, but the total length of body (without wings) and the maximum width of the abdomen are significantly greater in females than in males. Females are significantly heavier than males by about 4.8 mg. (mean weight of males 23.23 mg., females 28.06 mg.). For dry weight this difference is about 2.4 mg. (mean males 13.05 mg., females 15. 48 mg.). The mean moisture-content of body is about 43.5% of wet weight in males and 44.8 % in females, the sexual difference being only poorly significant. In both species, no correlation was found between headwidth and total body- length (without wings).